EFFICACY OF TRANSEPITHELIAL ACCELERATED COLLAGEN CROSS LINKING IN STOPPING THE PROGRESSION OF KERATOCONUS - Ahmad, Imran; Gul, Nazli; Khan, Bilal; Khan, Jahandad; Rasheed, Mutasim; Khan, Fahad (Journal of Ayub Medical College Abbottabad, 2024)
Background: Keratoconus is a progressive ectatic disease of the cornea leading to central corneal thinning, protrusion and permanent visual impairment in untreated cases. It is affecting young children with strong association to vernal keratoconjunctivitis a common disease of Asian countries. Corneal collagen cross linkage (CXL) is standard procedure to stop progression of keratoconus. In this research article we used trans-epithelial accelerated corneal cross-linking to check its efficacy in stopping the progression of disease as quick and safe procedure with less chances of complication than standard CXL protocol. Methods: The study was carried out in Khyber Teaching Hospital from November 2022-October 2023. The sample size calculated was 36 with sampling technique of non-probability consecutive convenience sampling method. Results: The mean age of the patients was 19.157±3.53 years. Post corneal cross-linking, at 6 months follow-up showed that in 94.44% of the patients, no progression of keratoconus was noted. Improvement in vision was recorded in 44.44% of patients. A positive correlation was detected between pre- and post-treatment patients in visual acuity, keratometry and pachymetry. Conclusion: The trans-epithelial accelerated corneal collagen crosslinking is a safe and quick procedure for stopping the progression of keratoconus associated with less morbidity and complications.